Epidemiological and Clinical Characterization of Idiopathic Gingival Papillokeratosis with Crypt Formation (IGPCF) - Garrocho-Rangel, Arturo (2026)
To clinically and epidemiologically characterize idiopathic gingival papillokeratosis with crypt formation (IGPCF) in a cohort of patients, aiming to enhance understanding and improve diagnosis and management of this rare condition. A cross-sectional study was conducted at the Diagnostic Clinic of the School of Stomatology, UASLP, between August 2022 and April 2023, including patients with complete electronic medical records containing demographic and medical information. Clinical diagnosis was supported by photographic documentation and cytological examination to rule out other pathologies. Group comparisons were performed with chi-square or Fisher’s exact tests. Logistic regression was applied to assess associations. A total of 7,163 patients were analyzed; the overall prevalence of IGPCF was 1.01% (95% CI: 0.79-1.26). Women had nearly a threefold higher likelihood of presenting IGPCF compared with men (OR=2.99, 95% CI: 1.76-5.10; p<0.05). No significant associations were found with age, smoking, alcohol use, or diabetes. Lesions were predominantly located in the maxilla (89.7%) and bilateral in 62.8% of cases. Mild gingival inflammation was observed in most evaluated cases. Clinically, lesions appeared as asymptomatic, pale-yellow, papillary plaques along the mucogingival junction. IGPCF is a rare, typically asymptomatic gingival condition with a distinct bilateral presentation in the maxillary gingiva, mostly affecting young adults. Proper identification is essential to prevent misdiagnosis. This study contributes the largest clinical dataset to date on IGPCF, reinforcing the need for standardized diagnostic criteria to support accurate clinical recognition and effective management.